A Survey of Papers Presented at the International Conference for the 85th Anniversary of Professor Olga Popova “Art of the Byzantine World” - Smirnova, Engelina S.; Zakharova, Anna V.; Pshenichnyi , Petr V. (Actual Problems of Theory and History of Art, 2023)
The paper surveys communications presented at the International conference for the 85th anniversary of professor Olga Popova “Art of the Byzantine World” held on September 27–29 at the State Institute for Art Studies in Moscow. The papers by Russian and foreign specialists dealt with a wide range of problems regarding the artistic culture of Byzantium, Old Rus’ and Christian East: architecture, painting, sculpture, minor arts, and manuscripts. The chronology of the researches ranges from the Late Antiquity to the Late Middle Ages. Some papers were centered on the problems of historiography and methodology, as well as the results of technological researches on icons kept in major museums of Russia.
Keywords: Olga Popova; Art of the Byzantine world; State Institute for Art Studies; Byzantine art; Old Russian art